Diagnostic paths and service needs of children with autism spectrum disorder and with other neurodevelopmental disorders in Bulgaria - Barokova, Mihaela D.; Andreeva-Sapundzhieva, Ana; Andonova, Elena; Markova-Derelieva, Galina; Karpur, Arun (Frontiers in Psychiatry, 2022)
Currently, there are no official statistics about the number of children with developmental disorders in Bulgaria. This is the first systematic investigation of the needs, access to services, and priorities of families of children with developmental disorders in the country. The study aims to: 1)characterize the needs of children with developmental disorders in Bulgaria; 2)to compare the needs and access to services of children with Autism Spectrum Disorders (ASD) and other neurodevelopmental disorders (oNDD); 3)and to examine the daily burden of their caregivers and how it varies based on their demographic characteristics, such as income and education. We used an online family needs assessment survey to collect data from caregivers of children with developmental disorders in Bulgaria between April and July 2020. 195 parents of children with ASD and 73 parents of children with oNDD completed the questionnaire. Children with ASD waited longer than children with oNDD to receive a diagnosis. Caregivers in the ASD group also expressed first concerns about their child’s development when their children were older and for different reasons than caregivers in the oNDD group. There were no significant differences between groups in service encounters, including access to and delay of medical, counseling, and educational services, with approximately 50% of all caregivers experiencing some delay and/or difficulties in access to services. There were no associations between access to services and caregiver education and family income, with the exception of higher education being linked to receiving a diagnosis earlier for the oNDD group. This study has three main findings: 1)children with ASD and children with oNDD in Bulgaria have different needs and paths to diagnosis; 2)nevertheless, children in both groups experience similar challenges to accessing medical, counseling, and educational services, regardless of their demographic characteristics; and 3)parents’ priorities focus on education, counseling, and medical support, protecting children’s basic rights, and raising awareness. A comparison of our findings to past research in the region shows a relative improvement in diagnostic services with families not having to travel outside their city to receive a diagnosis. Based on our findings, we provide specific recommendations for changes in services and policy.